2021
DOI: 10.1080/16078454.2021.1892329
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life in patients with nonvalvular atrial fibrillation treated with oral anticoagulants

Abstract: Objectives: Health-related quality of life (HRQL) is a key factor in making anticoagulant treatment decisions. The objective of this study was to assess the HRQL of patients with nonvalvular atrial fibrillation by treatment type: direct oral anticoagulants (DOACs) or vitamin K antagonists (VKAs). Methods: We carried out a cross-sectional observational study with clinical practice data, gathering demographic and clinical variables. HRQL was measured using the 5-level 5dimension EuroQol questionnaire (EQ-5D-5L).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Another limitation is that the clinical scenario required dyads to role-play a scenario that may not occur in clinical practice, where a patient is seeking advice from the physician about treating pain while on an anticoagulant. While this scenario may be infrequent in most practice settings, previous studies have found this to occur in up to 25% of patients receiving warfarin [ 2 , 3 ]. Furthermore, many physicians in the study indicated they were aware of the interaction when researchers explained the scenario prior to the simulated visit.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another limitation is that the clinical scenario required dyads to role-play a scenario that may not occur in clinical practice, where a patient is seeking advice from the physician about treating pain while on an anticoagulant. While this scenario may be infrequent in most practice settings, previous studies have found this to occur in up to 25% of patients receiving warfarin [ 2 , 3 ]. Furthermore, many physicians in the study indicated they were aware of the interaction when researchers explained the scenario prior to the simulated visit.…”
Section: Discussionmentioning
confidence: 99%
“…Warfarin is well known for having a multitude of drug-drug interactions (DDIs), with many avoided through health care provider awareness. However, studies found that up to 24% of people taking warfarin also received a prescription for nonsteroidal anti-inflammatory drugs (NSAIDs), and almost 50% of patients on warfarin have some form of ongoing pain [ 2 , 3 ]. Concomitant use of a NSAID and warfarin increases the risk of bleeding [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…What still needs to be considered when using anticoagulant drugs is the increased risk of bleeding, especially major bleeding that may require hospitalization, blood transfusion, and surgical intervention, or major bleeding involving important anatomical locations, such as intracranial hemorrhage, which is significantly related to increased mortality. [ 16 ] Therefore, not all NVAF patients are suitable targets for anticoagulation, and some NVAF patients are only suitable for short-term anticoagulation. Therefore, the study of non-pharmacological treatment of NVAF patients is also crucial, because the thrombosis of NVAF patients is most common in the left atrial appendage, so LAAO has become a potential non-pharmacological treatment for stroke prevention in NVAF patients.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have also confirmed that standard anticoagulation therapy can significantly reduce the risk of embolism in NVAF patients. What still needs to be considered when using anticoagulant drugs is the increased risk of bleeding, especially major bleeding that may require hospitalization, blood transfusion, and surgical intervention, or major bleeding involving important anatomical locations, such as intracranial hemorrhage, which is significantly related to increased mortality [16] . Therefore, not all NVAF patients are suitable targets for anticoagulation, and some NVAF patients are only suitable for short-term anticoagulation.…”
Section: Discussionmentioning
confidence: 99%
“…Gabilondo (2021) 78 Estudio transversal que incluyó 333 pacientes, de los que 126 tomaban ACOD y 207 AVK. El tratamiento con ACOD se asoció con menos ansiedad y depresión Domínguez-Erquicia (2021) 79 Registro multicéntrico (3 áreas sanitarias de España) de pacientes nonagenarios con FA no valvular anticoagulados con AVK o ACOD entre 2013 y 2017.…”
Section: Estudio (Año Publicación) Comentariounclassified